2021
DOI: 10.3897/rethinkingecology.6.56285
|View full text |Cite
|
Sign up to set email alerts
|

Failure to respond to a coral disease epizootic in Florida: causes and consequences

Abstract: Stony coral tissue loss disease (SCTLD) was first observed in September 2014 near Virginia Key, Florida. In roughly six years, the disease spread throughout Florida and into the greater Caribbean basin. The high prevalence of SCTLD and high resulting mortality in coral populations, and the large number of susceptible species affected, suggest that this outbreak is one of the most lethal ever recorded. The initial recognition and management response to this catastrophic disease in Florida was slow, which delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 115 publications
0
15
0
Order By: Relevance
“…These surveys will also help to identify which coral species could suffer local extinctions and provide recommendations to marine resource managers for the treatment of corals with antibiotics (Aeby et al, 2019;Neely et al, 2020) and the adoption of other measures such as coral rescue facilities (Zoccola et al, 2020;Florida Department of Environmental Protection, 2021), to prevent loss of these species locally. Furthermore, this study highlights the need for early detection and rapid response to disease outbreaks (Precht, 2021). In less than 5 months between AGRRA surveys of Grand Bahama in October 2019 and rapid assessments of reefs in March 2020, SCTLD had not only become established in the study area but had also spread over reefs along at least 75 km of the southern shoreline of Grand Bahama.…”
Section: Discussionmentioning
confidence: 81%
“…These surveys will also help to identify which coral species could suffer local extinctions and provide recommendations to marine resource managers for the treatment of corals with antibiotics (Aeby et al, 2019;Neely et al, 2020) and the adoption of other measures such as coral rescue facilities (Zoccola et al, 2020;Florida Department of Environmental Protection, 2021), to prevent loss of these species locally. Furthermore, this study highlights the need for early detection and rapid response to disease outbreaks (Precht, 2021). In less than 5 months between AGRRA surveys of Grand Bahama in October 2019 and rapid assessments of reefs in March 2020, SCTLD had not only become established in the study area but had also spread over reefs along at least 75 km of the southern shoreline of Grand Bahama.…”
Section: Discussionmentioning
confidence: 81%
“…Orbicellids are not listed as highly susceptible species to SCTLD (Florida Keys National Marine Sanctuary, 2018). Highly susceptible species include Pseudodiploria strigosa, Dendrogyra cylindrus, Meandrina meandrites, and Dichocoenia stokesii (Precht et al, 2016;Alvarez-Filip et al, 2019;Weil et al, 2019;Precht, 2021). However, Meiling et al (2021) observed regional differences in the species response to SCTLD for shallow-water reefs.…”
Section: Discussionmentioning
confidence: 99%
“…The reality is that SCTLD is not likely to be the last highly virulent coral disease to strike a reef system and a better understanding of how physiologic stress impacts coral immunity might lead to predictors that could be used in monitoring projects. Quicker response times to a coral disease outbreak could assist with mitigating the impact and prevent spread (Precht, 2021). Utilizing more citizen science through uploading photos/video to a central database could help, but one issue is that experts in the field have limited time for analyzing this type of data.…”
Section: Discussionmentioning
confidence: 99%
“…A number of environmental factors have been investigated concerning the emergence of the disease, which include increased sea surface temperatures (SSTs), increased turbidity from a concurrent dredging project (Miller et al, 2016;Gintert et al, 2019;Precht, 2021), and eutrophication (Dougan et al, 2020). Eutrophication from nutrient run off in the South Florida region, may have led to a reduction in immune function making corals susceptible to infection (Dougan et al, 2020).…”
Section: Sctld: What We Knowmentioning
confidence: 99%